2021
DOI: 10.1093/bib/bbaa387
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of cepharanthine against a SARS-CoV-2-related coronavirus

Abstract: Antiviral therapies targeting the pandemic coronavirus disease 2019 (COVID-19) are urgently required. We studied an already-approved botanical drug cepharanthine (CEP) in a cell culture model of GX_P2V, a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-related virus. RNA-sequencing results showed the virus perturbed the expression of multiple genes including those associated with cellular stress responses such as endoplasmic reticulum (ER) stress and heat shock factor 1 (HSF1)-mediated heat shock … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…In addition to molnupiravir and paxlovid, three more oral anti-COVID-19 drugs are in phase 3 clinical trials: the 3CL protease inhibitors s217622 (developed by Shionogi, Japan), the RdRp inhibitor AT-527 (jointly developed by Roche, Switzerland and Atea, USA), and the SARS-CoV-2 ACE2 and TMPRSS2 antagonist proxalutamide (initiated by Kintor Pharma, China) ( 14 ). Moreover, our group found that cepharanthine can effectively inhibit the entry and replication of GX_P2V, which has high homology with SARS-CoV-2, showing the potential antiviral activity of cepharanthine against SARS-CoV-2 ( 97 , 98 ). Zhang et al.…”
Section: Conclusion and Perspectivementioning
confidence: 98%
“…In addition to molnupiravir and paxlovid, three more oral anti-COVID-19 drugs are in phase 3 clinical trials: the 3CL protease inhibitors s217622 (developed by Shionogi, Japan), the RdRp inhibitor AT-527 (jointly developed by Roche, Switzerland and Atea, USA), and the SARS-CoV-2 ACE2 and TMPRSS2 antagonist proxalutamide (initiated by Kintor Pharma, China) ( 14 ). Moreover, our group found that cepharanthine can effectively inhibit the entry and replication of GX_P2V, which has high homology with SARS-CoV-2, showing the potential antiviral activity of cepharanthine against SARS-CoV-2 ( 97 , 98 ). Zhang et al.…”
Section: Conclusion and Perspectivementioning
confidence: 98%
“…Among the 231 articles (PubMed and Google Scholar), 91 were retained [ 3 , 12 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ,…”
Section: Update (16 June 2021) On Studies With Fiasmas In the Sars-cov-2 Infectionmentioning
confidence: 99%
“…This alkaloid inhibits SARS-CoV-2 entry in vitro at an IC 50 of 0.35 μM without any evident toxicity profile (selectivity index, [SI] > 70) [ 136 ]. Furthermore, the cell death cascade induced by the cellular stress response is another key target for SARS-CoV-2 [ 137 ]. It is worth noting that this bisbenzylisoquinoline alkaloid, with a good safety profile, is an approved drug in Japan since the 1950s and is used to treat acute and chronic diseases [ 132 ], highlighting that cepharanthine can serve as a potential therapeutic candidate for the treatment of SARS-CoV-2 infection.…”
Section: Natural Products In Combination With the Fda-approved Drugs Inhibit Sars-cov-2mentioning
confidence: 99%